On Finite Time Sensor Scheduling for Remote State Estimation With Energy Constraint - Wei, Jiang; Ye, Dan (2021 4th IEEE International Conference on Industrial Cyber-Physical Systems (ICPS), 2021)
In this paper, an energy-limited sensor schedule problem for remote estimation over a finite time horizon is considered in cyber-physical systems (CPSs). The sensor sends its local estimates to the remote estimator through a wireless network. At each time instant, the sensor decides whether it should send data or not so as to minimize the estimation error subject to limited communication resources. In this study, both the perfect communication channel and an unreliable channel are investigated. For the first situation, the optimal schedule scheme is presented as an explicit form. For the second one, an integer programming problem is formulated to get the optimal schedule sequence directly. At last, numerical examples are given to show the effectiveness of theoretical results.